2021 Clinical Practice Guidelines for Diabetes Mellitus of the Korean Diabetes Association - Hur, Kyu Yeon; Moon, Min Kyong; Park, Jong Suk; Kim, Soo-Kyung; Lee, Seung-Hwan; Yun, Jae-Seung; Baek, Jong Ha; Noh, Junghyun; Lee, Byung-Wan; Oh, Tae Jung; Chon, Suk; Yang, Ye Seul; et al. (Diabetes & metabolism journal, 2021)
The Committee of Clinical Practice Guidelines of the Korean Diabetes Association (KDA) updated the previous clinical practice guidelines for Korean adults with diabetes and prediabetes and published the seventh edition in May 2021. We performed a comprehensive systematic review of recent clinical trials and evidence that could be applicable in real-world practice and suitable for the Korean population. The guideline is provided for all healthcare providers including physicians, diabetes experts, and certified diabetes educators across the country who manage patients with diabetes or the individuals at the risk of developing diabetes mellitus. The recommendations for screening diabetes and glucose-lowering agents have been revised and updated. New sections for continuous glucose monitoring, insulin pump use, and non-alcoholic fatty liver disease in patients with diabetes mellitus have been added. The KDA recommends active vaccination for coronavirus disease 2019 in patients with diabetes during the pandemic. An abridgement that contains practical information for patient education and systematic management in the clinic was published separately.